An overview of Romanian agricultural indicators in the last years - Elena Bularca; Elena Toma (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The main purpose of this study is to present and analyze a number of technical and economic indicators of Romanian agriculture during 2005-2016. The main indicators monitored are the land fund development, area and crop production, livestock and livestock production, number of agricultural holdings, economic accounts and prices in agriculture and agro-environmental indicators. It was found that over time in Romanian agriculture were produced important changes both in terms of quantity and quality, both in crop farming and in livestock. Common Agricultural Policy attempts to provide a reasonable level of living of farmers and residents of countries default and especially for this reason, through the indicators analyzed, this study aims to provide a broad picture of progress or regress in Romanian agriculture in lately. The best perspective on agriculture is provided by economic accounts because they provide information about the composition and structure of agricultural production, the income received by farmers, the relationships between prices and inputs, the value of the standard output production, intermediate consumption, gross value added and subsidies practically with the help of these indicators is carried out an analysis of the economic efficiency of agriculture.
Keywords: Q11; Q12; Q17; O11; O13; 330; economic indicators; agriculture; efficiency